Fractional flow reserve measurements and long-term mortality—results from the FLORIDA study - Boeckling, Felicitas; Stähli, Barbara E.; Rudolph, Tanja; Lutz, Matthias; Schatz, Anne-Sophie; Vogelmann, Tobias; Stueve, Magnus; West, Nick E. J.; Boone, Els; Erbay, Aslihan; Leistner, David M. (Frontiers in Cardiovascular Medicine, 2024)
Randomized evidence suggested improved outcomes in fractional flow reserve (FFR) guidance of coronary revascularization compared to medical therapy in well-defined patient cohorts. However, the impact of FFR-guided revascularization on long-term outcomes of unselected patients with chronic or acute coronary syndromes (ACS) is unknown.The FLORIDA (Fractional FLOw Reserve In cardiovascular DiseAses) study sought to investigate outcomes of FFR-guided versus angiography-guided treatment strategies in a large, real-world cohort.This study included patients enrolled into the German InGef Research Database. Patients undergoing coronary angiography between January 2014 and December 2015 were included in the analysis. Eligible patients had at least one inpatient coronary angiogram for suspected coronary artery disease between January 2014 and December 2015. Patients were stratified into FFR arm if a coronary angiography with adjunctive FFR measurement was performed, otherwise into the angiography-only arm. Matching was applied to ensure a balanced distribution of baseline characteristics in the study cohort. Patients were followed for 3 years after index date and primary endpoint was all-cause mortality.In the matched population, mortality at 3 years was 9.6 % in the FFR-assessed group and 12.6 % in the angiography-only group (p = 0.002), corresponding to a 24 % relative risk reduction with use of FFR. This effect was most pronounced in patients in whom revascularization was deferred based on FFR (8.7 % vs.12.3 %, p = 0.04) and in high-risk subgroups including patients aged ≥ 75 years (14.9 % vs. 20.1 %, p < 0.01) and those presenting with ACS (10.2 % vs.14.0 %, p = 0.04). Conclusions FFR-based revascularization strategy was associated with reduced mortality at 3 years. These findings further support the use of FFR in everyday clinical practice.